Integer Programming Model in Handling IT Incident Workload - Mohd Nizamuddin Abas; Siti Haida Ismail; Haslaile Abdullah (International Journal of Applied Business and Information Systems, 2020)
A system called Incident Ticket System (ITS) uses in an organization to identify issue about service failure of IT system. The IT support personnel or team is responsible to resolve an incident associated with the ticket. The ticket has different kind of complexity which takes different time to solve and different level of expertise to close it. Therefore, allocating the optimum quantity of tickets to the right team members is vital in order to close all ticket at minimum time. Balancing the amount of ticket that each team member should get respectively with the ticket severity is important. To make even-handed workload for each team member, an approach of Integer Programming (IP) was applied in allocating the IT incident ticket. The IP model was implemented in Microsoft Excel software by using SOLVER. The computational results show that the proposed IP model was capable on solving allocation of ticket-severity problem.